UiTM International Conference on e-Learning : Programme Handbook : i-Learn Centre : 12th-14th December 2007 / University Teknologi MARA, UiTM - UiTM, Universiti Teknologi MARA (Pusat Percetakan, UiTM, 2007)
The conference theme is very significant and interesting as we are now facing the wave of globalization. The event aims to bring stakeholders on one platform through keynotes, papers, exhibitions and also to provide an excellent opportunity for participants to interact with the private sector, practitioners, government executives, academicians and experts. Integrating technologies in education involves comprehensive and coherent frameworks, policies and processes which can determine why and how technology should be utilized in education. This conference will help to identify level of higher learning institutions in incorporating e-learning development from policy aspects, governance, infrastructure, issues and pedagogy practices as well as human development.